The use of computers in agricultural production - Ibrahim, Mohd Yusof; Bidin, Abdul Rahman (1983)
The agricultural production activity, in general, encompasses a multiplicity of simplified processes accomplished along predetermined path or pattern. The performance is monitored and productivity measured with the objective to achive the ultimate economic benefit. The computer plays a role in assisting these processes, directly or indirectly, both at the farm as well as national level. Computers are used as a tool in farm management in the traditional batch mode and in on-line function, possibly with on-line control, for specific applications. Statistics related to projetions, policy implementation and review, and to indirect control of production are gathered and analysed at national level using larger computers.